Congenital disorder of glycosylation with defective fucosylation 2 (FCSK gene defect): The third report in the literature with a mild phenotype - Abeer Al Tuwaijri; Yusra Alyafee; Muhammad Umair; Arwa Alsubait; Mashael Alharbi; Hamad AlEidi; Mariam Ballow; Mohammed Aldrees; Qamre Alam; Abdulkareem Al Abdulrahman; Muhammad Talal Alrifai; Majid Alfadhel (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Congenital disorders of glycosylation (CDG) are a group of heterogeneous disorders caused by abnormal lipid or protein glycosylation. Variants in the FCSK gene have been reported to cause CDG. Defective FCSK‐induced CDG (FCSK–CDG) has only been reported previously in three unrelated children. Methods In this study, we genetically and clinically examined a 3‐year‐old proband with resolved infantile spasms and normal development. Standard whole‐exome sequencing (WES) and Sanger sequencing were performed to identify the functional impact of the variant. Results WES revealed a rare biallelic missense variant (c.3013G>C; p.Val1005Leu) in FCSK. RT‐qPCR showed a significant depletion in FCSK gene expression in the affected individual. Western blotting revealed reduced FCSK expression at the protein level compared to that in the control. Furthermore, 3D protein modeling suggested changes in the secondary structure, which might affect the overall FCSK protein function. Conclusion This study broadens the mutation and phenotypic spectrum of FCSK‐associated developmental disorders.